Food security and nutrition inequities in the context of agricultural commercialisation in Sub-Saharan Africa: A narrative literature review - Gordon, Jessica (Institute of Development Studies, 2022)
Many sub-Saharan African countries are choosing to prioritise market-oriented agricultural production as a central component of their agricultural and economic development strategies. An increasing focus on inequity in international development research has in part been driven by the observation of persistent and worsening marginalisation of particular groups. In some cases this has been linked to agricultural commercialisation processes (i.e. farmers becoming increasingly market-oriented) and unequal food security and nutrition outcomes in sub-Saharan Africa. This narrative literature review addresses the question: what are the different forms and processes of inequity seen to influence unequal food security and nutrition outcomes in the context of agricultural commercialisation in sub-Saharan Africa? The review findings point to a rich and diverse set of literature exploring various dimensions of inequity in relation to agricultural commercialisation, food security and nutrition in sub-Saharan Africa. To facilitate exploration of these dimensions, and drawing on other recent equity literature framings, inequities are conceptualised and examined at three intersecting levels: (1) unequal food security and nutrition outcomes based on social position, (2) underlying material circumstances, and (3) basic structural causes. The review provides a first step to advancing theoretical understandings around these three intersecting areas and suggests further research is needed to explore and define inequities and further develop the conceptual framework. This is considered a critical priority to mitigate against and reverse existing food security and nutrition inequities that might in part be attributed to agricultural commercialisation processes.